Migration Policy Uncertainty and Terrorist Attacks: Evidence from the US - An, Zhen (International Journal of Social and Administrative Sciences, 2019)
To examine the potential relationship between migration policy uncertainty and terrorist attacks, this study uses the migration policy uncertainty index based on newspaper coverage frequency under the empirical framework of Vector Autoregression (VAR) model. The main findings of this study are as follows: (1) Based on the Granger causality test, migration policy uncertainty increases the occurrence of terrorist attacks. (2) From impulse response analysis, the exogenous shock to migration policy uncertainty has a significant and persistent impact on terrorist attacks. (3) By forecast error variance decomposition, migration policy uncertainty contributes to more than 24% of the forecast error variance of terrorist attacks. (4) The nexus between migration policy uncertainty and terrorist attacks only exists in typical migration countries, such as the U.S. Therefore, this paper first documents the causal relationship between terrorist attack and migration policy uncertainty. In practice, policymakers should decrease migration policy uncertainty in order to prevent the likelihood of future terrorist attacks.